Thermoplastic elastomer composition

JP7636218B2Active Publication Date: 2025-02-26SUMITOMO CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021044541
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-23
Filing Date
2021-03-18
Publication Date
2025-02-26
Estimated Expiration
2041-03-18

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、低温耐衝撃性と高温耐衝撃性とが高いレベルで両立した成形体を得ることができ、エアバッグ収納カバー等の各種用途に好適に使用できる、熱可塑性エラストマー組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636218000001
    Figure 0007636218000001
  • Figure 0007636218000002
    Figure 0007636218000002
  • Figure 0007636218000003
    Figure 0007636218000003
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition that can form a molded article having both of low-temperature impact resistance and high-temperature impact resistance at high levels.SOLUTION: The present disclosure provides a thermoplastic elastomer composition. The thermoplastic elastomer composition is injection-molded into a mold cavity of 90 mm wide×150 mm long×2.0 mm thick at a cylinder temperature of 220°C, a mold temperature of 50°C, and an injection rate of 25 cm3 / sec to make a molded article. The vicinity of a central portion of the molded article is punched out in a size of 30 mm wide×30 mm long×2.0 mm thick to make a specimen that satisfies the following requirements: (1) an area increase rate S of the specimen after impregnation with petroleum benzine at 23°C for 24 hours is 20% or less; and (2): a volume increase rate V of the specimen after impregnation with petroleum benzine at 23°C for 24 hours is 20% or more and 125% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer composition. [Background technology]

[0002] Thermoplastic elastomer compositions containing an ethylene-based polymer component and a propylene-based polymer component are used as materials for airbag storage covers (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-265628 [Patent Document 2] JP 2000-72937 A [Patent Document 3] JP 2001-279030 A [Patent Document 4] JP 2002-194098 A Summary of the Invention [Problem to be solved by the invention]

[0004] One of the characteristics strongly required for an airbag storage cover is impact resistance. Since the inside of a vehicle in which the airbag storage cover is used can be subject to both high and low temperatures, it is preferable that the airbag storage cover has high impact resistance at both high and low temperatures. Under such circumstances, the problem to be solved by the present invention is to provide a thermoplastic elastomer composition which can give a molded article having both high levels of low-temperature impact resistance and high-temperature impact resistance. [Means for solving the problem]

[0005] The present inventors have conducted intensive research in light of the above background and have completed the present invention. That is, the present invention provides: [1] A thermoplastic elastomer composition, the thermoplastic elastomer composition being extruded at a cylinder temperature of 220°C, a mold temperature of 50°C, and an injection rate of 25 cm 3 The molded article was injection-molded into a mold cavity of 90 mm width × 150 mm length × 2.0 mm thickness under conditions of 0.15 s / sec to obtain a molded article, and a test piece of 30 mm width × 30 mm length × 2.0 mm thickness was punched out from near the center of the molded article. The test piece was a thermoplastic elastomer composition that satisfied the following requirements (1) and (2). Requirement (1): The test piece has an area increase rate S of 20% or less after being immersed in petroleum benzine at 23°C for 24 hours. Requirement (2): The test piece has a volume increase rate V of 20% or more and 125% or less after being immersed in petroleum benzine at 23° C. for 24 hours.

[0006] Below, [2] to [9] are each preferred aspects or embodiments of the present invention. [2] The thermoplastic elastomer composition according to [1], comprising an ethylene-based polymer component (A) and a propylene-based polymer component (B). [3] The ethylene polymer component (A) contains one or more ethylene polymers selected from the group consisting of the following components (A1), (A2), and (A3), and the fusion enthalpy ΔH of the ethylene polymer component (A) observed in a temperature range of 70° C. or more and 140° C. or less by differential scanning calorimetry is mA The thermoplastic elastomer composition according to [2], wherein the thermal expansion coefficient is 1 J / g or more and 115 J / g or less. Component (A1): amorphous ethylene polymer; Component (A2): a crystalline ethylene polymer containing 90% by weight or more of structural units derived from ethylene; Component (A3): A crystalline ethylene copolymer in which the content of structural units derived from ethylene is 50% by weight or more and less than 90% by weight. [4] The fusion enthalpy ΔH observed in the temperature range of 70°C to 200°C by differential scanning calorimetry m1The thermoplastic elastomer composition according to any one of [1] to [3], wherein the compressive strength is 115 J / g or less. [5] The fusion enthalpy ΔH observed in the temperature range of 70°C to 140°C by differential scanning calorimetry m2 The thermoplastic elastomer composition according to any one of [1] to [4], wherein the thermoplastic elastomer composition has a modulus of 1 J / g or more. [6] Component (B) is the intrinsic viscosity of the insoluble matter ([η cxis The thermoplastic elastomer composition according to any one of [2] to [5], comprising a propylene-based polymer (B2) having a viscosity index (SPA) of 1.5 dl / g or more and 7.5 dl / g or less. [7] The intrinsic viscosity ([η cxis ]) is 1.5 dl / g or more and 6.0 dl / g or less. [8] The thermoplastic elastomer composition according to any one of [1] to [7], which satisfies the following requirement (1'): Requirement (1'): The test piece has an area increase rate S of 4% or more and 15% or less after being immersed in petroleum benzine at 23°C for 24 hours. [9] The thermoplastic elastomer composition according to any one of [1] to [8], which satisfies the following requirement (2'): Requirement (2'): The test piece has a volume increase rate V of 55% or more and 115% or less after being immersed in petroleum benzine at 23°C for 24 hours.

[10] A molded article comprising the thermoplastic elastomer composition according to any one of [1] to [9].

[11] An airbag storage cover comprising the thermoplastic elastomer composition according to any one of [1] to [9]. Effect of the Invention

[0007] According to the present invention, it is possible to obtain a molded article having both high levels of low-temperature impact resistance and high-temperature impact resistance, and it is possible to provide a thermoplastic elastomer composition that can be suitably used for various applications such as airbag storage covers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The thermoplastic elastomer composition of the present invention is prepared by subjecting the thermoplastic elastomer composition to a cylinder temperature of 220°C, a mold temperature of 50°C, and an injection rate of 25 cm 3 The molded product is injection molded into a mold cavity of 90 mm wide x 150 mm long x 2.0 mm thick at a temperature of 100 / s, and a pressure of 200 / s is applied to obtain a molded product. In order to obtain a molded product with a filling rate sufficient for appropriate measurement, a sufficient holding pressure is applied to prevent sink marks. A test piece of 30 mm wide x 30 mm long x 2.0 mm thick is obtained by punching out the center of the molded product, and the test piece satisfies the following requirements (1) and (2). Requirement (1): The test piece has an area increase rate S of 20% or less after being immersed in petroleum benzine at 23°C for 24 hours. Requirement (2): The test piece has a volume increase rate V of 20% or more and 125% or less after being immersed in petroleum benzine at 23° C. for 24 hours. The thermoplastic elastomer composition used in injection molding may be in any form that allows injection molding, and various forms such as pellets and crushed molded products can be used.

[0009] Area increase rate S The area increase rate S was calculated according to JIS K6258 by immersing the above test piece in petroleum benzine at 23°C for 24 hours, measuring the length and thickness of the test piece, and calculating the area S 24 is calculated, and then further calculated according to the following formula: Area increase rate S: (S 24 / S0-1)×100 [%] (S0: area before impregnation with petroleum benzine (width x length), S 24 : Area after soaking in petroleum benzine (width x length)

[0010] As described above, the area increase rate S defined above in the present invention is 20% or less. When the area increase rate S is 20% or less and other conditions specified in the present invention are satisfied, a molded article having both high levels of low-temperature impact resistance and high-temperature impact resistance can be produced using the thermoplastic elastomer composition of the present invention. The area increase rate S is usually 0% or more, preferably 4% to 20%, more preferably 4% to 15%, and even more preferably 5% to 10%. The area increase rate S can be appropriately adjusted by, for example, the content, molecular weight, content and density of structural units derived from ethylene of component (A2) and component (A3) described later, the content, molecular weight and content of structural units derived from propylene of component (B2) described later, etc. When the content of components (A2) and (B2) described later is increased, the area increase rate S tends to decrease. In addition, it can be appropriately adjusted by the melt kneading conditions, particularly the presence or absence of dynamic crosslinking, etc.

[0011] Volume increase rate V The volume increase rate V was calculated according to JIS K6258 by immersing the above test piece in petroleum benzine at 23°C for 24 hours, measuring the width, length and thickness of the test piece, and calculating the volume V 24 is calculated, and then further calculated according to the following formula: Volume increase rate V:(V 24 / V0-1)×100 [%] (V0: volume before impregnation with petroleum benzine (width x length x thickness), V 24 : Volume after soaking in petroleum benzine (width x length x thickness)

[0012] As described above, the volume increase rate V defined in the present invention is 20% or more and 125% or less. When the volume increase rate V satisfies this condition and other conditions specified in the present invention are met, a molded article having both high levels of low-temperature impact resistance and high-temperature impact resistance can be produced using the thermoplastic elastomer composition of the present invention. The volume increase rate V is preferably 55% or more and 120% or less, more preferably 55% or more and 115% or less, and even more preferably 80% or more and 115% or less. The volume increase rate V can be appropriately adjusted, for example, by the contents of components (A1), (A2), and (A3) described below, the content of structural units derived from ethylene, and the density. It can also be appropriately adjusted by the contents of components (B1) and (B2) described below, the content of structural units derived from propylene, etc. It can also be appropriately adjusted by blending a nucleating agent, etc.

[0013] Enthalpy of fusion ΔH The thermoplastic elastomer composition of the present invention preferably has a melting enthalpy ΔH within a specific temperature range measured by differential scanning calorimetry, which is within a specific numerical range. The fusion enthalpy ΔH herein refers to the heat of fusion obtained by analyzing a portion of a melting curve within a predetermined temperature range measured by differential scanning calorimetry according to the following method in accordance with JIS K7122-1987.

[0014] (Measuring method of melting curve by differential scanning calorimetry) Using a differential scanning calorimeter, an aluminum pan containing about 5 mg of sample under a nitrogen atmosphere is (1) held at 220°C for 5 minutes, then (2) cooled from 220°C to -80°C at a rate of 10°C / min, then (3) held at -80°C for 10 minutes, and then (4) heated from -80°C to 220°C at a rate of 10°C / min. The differential scanning calorimeter curve obtained by the calorimetry in the process (4) is taken as the melting curve.

[0015] More specifically, the thermoplastic elastomer composition of the present invention has a melting enthalpy ΔH observed in a temperature range of 70° C. or more and 200° C. or less by differential scanning calorimetry. m1 It is preferable that the strength is 115 J / g or less. The fusion enthalpy ΔH observed in the temperature range of 70°C to 200°C by differential scanning calorimetry m1 It is preferable that the above range is satisfied from the viewpoints of low-temperature impact resistance, rigidity, etc. More specifically, the thermoplastic elastomer composition of the present invention has a melting enthalpy ΔH observed in a temperature range of 70° C. or more and 200° C. or less by differential scanning calorimetry. m1 However, it is more preferable that the elastic modulus is 35 J / g or more and 95 J / g or less, and further preferably 65 J / g or more and 85 J / g or less. Enthalpy of fusion ΔH m1 can be appropriately adjusted by the contents of components (A1), (A2), and (A3) described below, and the content and density of structural units derived from ethylene. It can also be appropriately adjusted by the contents of components (B1) and (B2) described below, and the content of structural units derived from propylene, etc. It can also be appropriately adjusted by blending a nucleating agent, etc.

[0016] The thermoplastic elastomer composition of the present invention has a melting enthalpy ΔH m2 It is preferable that the thermal expansion coefficient is 1 J / g or more. The fusion enthalpy ΔH observed in the temperature range of 70°C to 140°C by differential scanning calorimetry m2 It is preferable that the above range is satisfied from the viewpoints of high-temperature impact resistance, moldability, and the like. The thermoplastic elastomer composition of the present invention has a melting enthalpy ΔH m2 It is more preferable that the elastic modulus is 6 J / g or more, and further preferably 10 J / g or more and 25 J / g or less. Enthalpy of fusion ΔH m2 can be appropriately adjusted by the contents of components (A2) and (A3) described below, and the content and density of structural units derived from ethylene. In general, it tends to increase as the amount of crystalline ethylene polymer increases. It can also be appropriately adjusted by blending a nucleating agent, etc.

[0017] Shock-resistance The thermoplastic elastomer composition of the present invention satisfies the above-mentioned requirements (1) and (2), and therefore it is possible to produce a molded article exhibiting excellent impact resistance, in particular a molded article exhibiting both high levels of low-temperature impact resistance and high-temperature impact resistance. For example, the thermoplastic elastomer composition of the present invention is prepared by subjecting the thermoplastic elastomer composition to a cylinder temperature of 220° C., a mold temperature of 50° C., and an injection rate of 25 cm 3 It is preferable that a molded article obtained by injection molding into a mold cavity of 90 mm width × 150 mm length × 2.0 mm thickness under conditions of 1 / sec (the injection molded article before punching out the test specimens for measuring the above requirements (1) and (2)) exhibits high IZOD impact strength.

[0018] More specifically, the injection molded article has an IZOD impact strength of 10.0 kJ / m at -40°C. 2 It is preferable that the concentration is 20.0 kJ / m or more. 2 More preferably, it is 50.0 kJ / m or more. 2 More preferably, it is equal to or greater than this. The IZOD impact strength at −40° C. can be measured by a method commonly used in the art, for example, according to JIS K7110. In addition, the fracture morphology of the injection-molded body in the IZOD impact strength test is preferably either hinge fracture, i.e., incomplete fracture in which the test piece has lost its bending rigidity and only a hinge-like thin surface layer remains integral and inseparable, or partial fracture, i.e., incomplete fracture that does not meet the definition of hinge fracture described above.

[0019] Furthermore, the IZOD impact strength of the injection molded article at 85°C is 37.0 kJ / m 2 It is preferable that the concentration is 40.0 kJ / m or more. 2 More preferably, it is equal to or greater than this. The IZOD impact strength at 85° C. can also be measured by a method commonly used in the art, for example, according to JIS K7110. Furthermore, the fracture morphology of the injection molded article in the IZOD impact strength test is preferably partial fracture, that is, incomplete fracture that does not meet the definition of hinge fracture described above.

[0020] The thermoplastic elastomer composition of the present invention is not particularly limited as long as a test piece obtained from the thermoplastic elastomer composition under the above conditions satisfies the above requirements (1) and (2). However, it is preferable for the composition to contain an ethylene-based polymer component (A) and a propylene-based polymer component (B) described below.

[0021] Here, the ethylene-based polymer component (A) is a component consisting of a polymer containing 50% by weight or more of structural units derived from ethylene, and the propylene-based polymer component (B) is a component consisting of a polymer having a content of structural units derived from propylene of more than 50% by weight and not more than 100% by weight. The thermoplastic elastomer composition of the present embodiment may consist only of the ethylene-based polymer component (A) and the propylene-based polymer component (B), or may contain other components in addition to the ethylene-based polymer component (A) and the propylene-based polymer component (B). The contents of the ethylene-based polymer component (A) and the propylene-based polymer component (B) are not particularly limited, but when the total weight of the thermoplastic elastomer composition of the present embodiment is taken as 100% by weight, it is preferable that the ethylene-based polymer component (A) is contained in an amount of 20% by weight or more and 80% by weight or less, and the propylene-based polymer component (B) is contained in an amount of 20% by weight or more and 80% by weight or less. The content of the ethylene polymer component (A) is more preferably from 25% by weight to 75% by weight, further preferably from 30% by weight to 70% by weight, and particularly preferably from 35% by weight to 65% by weight. The content of the propylene polymer component (B) is more preferably from 25% by weight to 75% by weight, particularly preferably from 30% by weight to 70% by weight, and particularly preferably from 35% by weight to 65% by weight.

[0022] Ethylene-based polymer component (A) The ethylene-based polymer component (A) constituting the thermoplastic elastomer composition of the present embodiment is a component made of a polymer containing 50% by weight or more of structural units derived from ethylene. The polymer may consist of only one type of polymer containing 50% by weight or more of structural units derived from ethylene, or may consist of a combination of two or more types. The ethylene-based polymer constituting the ethylene-based polymer component (A) is not particularly limited as long as it contains 50% by weight or more of structural units derived from ethylene, but is preferably one or more ethylene-based polymers selected from the group consisting of components (A1), (A2), and (A3) described below. The ethylene polymer component (A) of the present embodiment may consist only of the components (A2) and (A3) described below, or may contain other components in addition to the components (A1), (A2), and (A3) described below. There are no particular limitations on the contents of components (A1), (A2), and (A3) described below. When the weight of the ethylene polymer component (A) of the present embodiment is taken as 100% by weight, the component (A1) is preferably contained in an amount of 0% by weight or more and 99% by weight or less, the component (A2) is preferably contained in an amount of 0% by weight or more and 45% by weight or less, and the component (A3) is preferably contained in an amount of 0% by weight or more and 100% by weight or less. The content of component (A1) is more preferably from 5% by weight to 85% by weight. The content of component (A2) is more preferably from 0 to 20% by weight, and further preferably from 5 to 20% by weight. The content of component (A3) is more preferably from 0 to 95% by weight, and further preferably from 0 to 90% by weight.

[0023] In the thermoplastic elastomer composition of the present embodiment containing the ethylene-based polymer component (A), the melting enthalpy ΔH of the ethylene-based polymer component (A) observed in a temperature range of 70° C. or more and 140° C. or less by differential scanning calorimetry is mA It is preferable that the thermal expansion coefficient is 1 J / g or more and 115 J / g or less. Melting enthalpy ΔH of ethylene polymer component (A) mAIt is preferable that the melting enthalpy ΔH is 1 J / g or more in terms of high temperature impact resistance, etc. mA If it is less than 1 J / g, the releasability from the mold during molding may deteriorate. The thermoplastic elastomer composition of the present invention has a melting enthalpy ΔH mA is more preferably 20 J / g or more, further preferably 27 J / g or more and 90 J / g or less, and particularly preferably 35 J / g or more and 60 J / g or less.

[0024] Melting enthalpy ΔH of ethylene polymer component (A) mA The method of calculating is the same as that described above for the melting enthalpy ΔH of the thermoplastic elastomer composition of the present invention. Enthalpy of fusion ΔH mA can be appropriately adjusted by adjusting the types and amounts of components (A1), (A2), and (A3) described below, and generally tends to decrease as the amounts of these crystalline components decrease. In addition, when the ethylene polymer component (A) is composed of a plurality of components, the fusion enthalpy ΔH mA is the arithmetic average value taking into account the fusion enthalpy and weight of the multiple components. For example, when the ethylene polymer component (A) is composed of the components (A1), (A2), and (A3) described below, the fusion enthalpy ΔH of the ethylene polymer component (A) is mA is the fusion enthalpy of each component, ΔH mA1 , ΔH mA2 , and ΔH mA3 and its weight W A1 , W A2 , and W A3 From this, it can be calculated according to the following formula: (ΔH mA1 W A1 +ΔH mA2 W A2 +ΔH mA3 W A3 ) / (W A1 +W A2 +WA3 )

[0025] The ethylene-based polymer constituting the ethylene-based polymer component (A) is not particularly limited as long as it contains 50% by weight or more of structural units derived from ethylene. However, it is preferable that the ethylene-based polymer is one or more ethylene-based polymers selected from the group consisting of the following components (A1), (A2), and (A3).

[0026] Amorphous ethylene polymer (A1) The amorphous ethylene polymer (A1) preferably used as all or a part of the ethylene polymer component (A) may be any ethylene polymer having a ratio of ethylene-derived structural units of 50% by weight or more and being amorphous at room temperature, and is not otherwise limited, but is preferably an amorphous ethylene-α-olefin copolymer (A1-1) and / or an ethylene-α-olefin-non-conjugated diene copolymer (A1-2) described in detail below. The amorphous ethylene polymer (A1) has a melting enthalpy of less than 10 J / g measured in a temperature range of 70°C to 140°C by differential scanning calorimetry.

[0027] Amorphous ethylene-α-olefin copolymer (A1-1) The amorphous ethylene-α-olefin copolymer (A1-1) preferably used as the amorphous ethylene polymer (A1) is an amorphous ethylene copolymer containing structural units derived from ethylene and structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms. Preferably, in the amorphous ethylene-α-olefin copolymer (A1-1), the content of structural units derived from ethylene is from 50% by weight to less than 90% by weight, and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is from 5% by weight to 50% by weight (where the total amount of the amorphous ethylene-α-olefin copolymer (A1-1) is taken as 100% by weight), and the Mooney viscosity (ML 1+4 ,125℃) is 15 to 40, and the density is 0.850g / cm 3 More than 0.890g / cm 3The amorphous ethylene / α-olefin copolymer (A1-1) may have two or more types of structural units derived from α-olefins having 4 or more carbon atoms.

[0028] The α-olefin having 4 or more carbon atoms in the amorphous ethylene-α-olefin copolymer (A1-1) is preferably an α-olefin having 4 to 8 carbon atoms, such as 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. The α-olefin having 4 to 8 carbon atoms is preferably 1-butene, 1-hexene, or 1-octene.

[0029] In the amorphous ethylene-α-olefin copolymer (A1-1), the content of structural units derived from ethylene is preferably from 50% by weight to less than 90% by weight, and more preferably from 52% by weight to 65% by weight, and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is preferably from 10% by weight to 50% by weight, and more preferably from 35% by weight to 48% by weight (wherein the total amount of the amorphous ethylene-α-olefin copolymer (A1-1) is 100% by weight). The content of structural units derived from ethylene in the amorphous ethylene-α-olefin copolymer (A1-1) and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms can be determined by nuclear magnetic resonance spectroscopy (NMR).

[0030] The density of the amorphous ethylene-α-olefin copolymer (A1-1) is preferably 0.850 g / cm 3 More than 0.890g / cm 3 From the viewpoints of the low-temperature impact resistance of the molded product and the dimensional stability when molded into a molded product, it is more preferably 0.850 g / cm or less. 3 More than 0.875g / cm 3 The following is the result.

[0031] Mooney viscosity (ML) of amorphous ethylene-α-olefin copolymer (A1-1) measured at 125°C 1+4 , 125°C) is preferably 20 or more and 30 or less from the viewpoint of low-temperature impact resistance.

[0032] Examples of methods for producing the amorphous ethylene-α-olefin copolymer (A1-1) include known polymerization methods using known olefin polymerization catalysts, such as a slurry polymerization method, a solution polymerization method, a bulk polymerization method, and a gas phase polymerization method using a complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, or a nonmetallocene complex.

[0033] Ethylene-α-olefin-non-conjugated diene copolymer (A1-2) The ethylene-α-olefin-non-conjugated diene copolymer (A1-2) preferably used as the amorphous ethylene polymer (A1) is a non-conjugated diene copolymer having structural units derived from ethylene, structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms, and structural units derived from a non-conjugated diene, and the content of structural units derived from ethylene is 50% by weight or more. In the ethylene-α-olefin-non-conjugated diene copolymer (A1-2), the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is 35% by weight or more and 50% by weight or less (wherein the total content of structural units derived from ethylene and structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms is taken as 100% by weight), the iodine value is 0.1 to 20, and the Mooney viscosity (ML 1+4 , 125° C.) is preferably 40 or more and 85 or less, and the molecular weight distribution (Mw / Mn) is preferably 1.5 or more and 3.5 or less.

[0034] The ethylene-α-olefin-non-conjugated diene copolymer (A1-2) can be produced by a known polymerization method using a known olefin polymerization catalyst, such as a slurry polymerization method, a solution polymerization method, a bulk polymerization method, or a gas phase polymerization method using a complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, or a nonmetallocene complex.

[0035] In order to adjust the molecular weight of the ethylene / α-olefin / non-conjugated diene copolymer (A1-2) to be produced, a molecular weight regulator such as hydrogen may be used.

[0036] The α-olefin having 4 or more carbon atoms in the non-conjugated diene copolymer of the ethylene-α-olefin-non-conjugated diene copolymer (A1-2) is preferably an α-olefin having 4 to 8 carbon atoms, such as 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. The α-olefin having 4 to 8 carbon atoms is preferably 1-butene, 1-hexene, or 1-octene. The α-olefin having 4 or more carbon atoms may be used alone or in combination of two or more.

[0037] Examples of non-conjugated dienes that provide structural units derived from non-conjugated dienes include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, and 5-isopropylidene-2-norbornene. Examples of such diphenyl ethers include cyclic non-conjugated dienes such as norbornene and 6-chloromethyl-5-isopropenyl-2-norbornene; and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, 1,3,7-octatriene and 1,4,9-decatriene, and preferably 5-ethylidene-2-norbornene, 5-vinylnorbornene, or dicyclopentadiene.

[0038] The content of structural units derived from ethylene in the ethylene-α-olefin-non-conjugated diene copolymer (A1-2) is preferably 50% by weight or more and 75% by weight or less, and from the viewpoint of low-temperature impact resistance of a molded article, more preferably 50% by weight or more and 65% by weight or less. The content of structural units derived from propylene in component (A1-2) is preferably 25% by weight or more and 50% by weight or less, and from the viewpoint of low-temperature impact resistance of a molded article, more preferably 35% by weight or more and 50% by weight or less (however, the total content of structural units derived from ethylene and structural units derived from propylene is taken as 100% by weight). The content of structural units derived from ethylene in the ethylene-α-olefin-non-conjugated diene copolymer (A1-2) and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms can be determined by nuclear magnetic resonance spectroscopy (NMR).

[0039] The ethylene-α-olefin-non-conjugated diene copolymer (A1-2) has a Mooney viscosity (ML 1+4, 125°C) is preferably from 40 to 85, more preferably from 43 to 75, and particularly preferably from 45 to 70. The Mooney viscosity is measured according to ASTM D-1646.

[0040] The iodine value of the ethylene-α-olefin-non-conjugated diene copolymer (A1-2) is preferably from 0.1 to 20, and from the viewpoint of the rigidity of a molded product, more preferably from 0.1 to 15, particularly preferably from 0.1 to 10. The iodine value refers to the number of grams of iodine used in the reaction between 100 g of a sample and iodine. The iodine value of the non-conjugated diene copolymer can be determined by infrared spectroscopy.

[0041] The molecular weight distribution of the ethylene-α-olefin-non-conjugated diene copolymer (A1-2) is preferably 1.5 or more and 3.5 or less, and from the viewpoint of low-temperature impact resistance of the molded product, more preferably 1.5 or more and 3.0 or less, and particularly preferably 1.5 or more and 2.3 or less. The molecular weight distribution is the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography, ie, Mw / Mn.

[0042] Component (A2): A crystalline ethylene polymer having 90% by weight or more of structural units derived from ethylene The crystalline ethylene polymer (A2), which is preferably used as the whole or part of the ethylene polymer component (A), is a crystalline (co)polymer containing 90 to 100% by weight of structural units (ethylene units) derived from ethylene. However, the weight of the entire crystalline ethylene polymer (A2) is taken as 100% by weight. Examples of the crystalline ethylene polymer (A2) include ethylene homopolymers, copolymers of at least one α-olefin having 3 to 10 carbon atoms (e.g., propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, and 1-hexene) and ethylene, and copolymers of at least one polar monomer (e.g., vinyl acetate, acrylic acid ester, and methacrylic acid ester) and ethylene. Examples of the crystalline ethylene polymer (A2) include preferably high-density polyethylene, low-density polyethylene, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-pentene copolymers, ethylene-4-methyl-1-pentene copolymers, and ethylene-1-hexene copolymers. The crystalline ethylene polymer (A2) has a melting enthalpy of usually 50 J / g or more, preferably 100 J / g or more, and more preferably 200 J / g or more, as measured by differential scanning calorimetry in a temperature range of 70° C. to 140° C. The melting enthalpy of the crystalline ethylene polymer (A2) in a temperature range of 70° C. to 140° C. is usually 300 J / g or less.

[0043] The melt flow rate of the crystalline ethylene polymer (A2) (measured according to JIS K6760 under a load of 21.18 N at a temperature of 190° C.) is preferably 0.01 to 300 g / 10 min, more preferably 0.1 to 200 g / 10 min.

[0044] When a high-density polyethylene is used as the crystalline ethylene polymer (A2), the high-density polyethylene is a polymer containing 90 to 100% by weight of a structural unit based on ethylene (ethylene unit) and has a density of 0.940 g / cm as measured in accordance with JIS K7112. 3 It is preferable that the weight of the high-density polyethylene is 100% by weight. The content of structural units derived from ethylene in the crystalline ethylene polymer (A2) and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms can be determined by nuclear magnetic resonance spectroscopy (NMR).

[0045] The melt flow rate of the high-density polyethylene (measured in accordance with JIS K6760 under a load of 21.18 N at a temperature of 190°C) is preferably 0.01 to 300 g / 10 min, more preferably 0.1 to 200 g / 10 min, still more preferably 0.5 to 50 g / 10 min, and particularly preferably 1 to 20 g / 10 min.

[0046] The high density polyethylene can be produced by a known polymerization method using a Ziegler-Natta catalyst, a metallocene catalyst, etc. as a polymerization catalyst. Examples of the polymerization method include a solution polymerization method, a bulk polymerization method, a slurry polymerization method, a gas phase polymerization method, etc., and two or more of these may be combined.

[0047] Component (A3): A crystalline ethylene copolymer in which the content of structural units derived from ethylene is 50% by weight or more and less than 90% by weight. (A3), which is preferably used as all or part of the component (A), is a crystalline ethylene copolymer in which the content of structural units derived from ethylene is 50% by weight or more and less than 90% by weight. Component (A3) is an olefin block copolymer containing an ethylene polymer block and an ethylene-α-olefin copolymer block. Component (A3) has a crystal melting peak at 70°C to 140°C and a melting enthalpy of preferably 10 to 70 J / g, more preferably 30 to 50 J / g.

[0048] The ethylene polymer block in component (A3) is mainly composed of ethylene units, but may have structural units derived from other monomers in addition to ethylene. Examples of structural units derived from other monomers include structural units derived from 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. Preferred are structural units derived from α-olefins having 3 to 8 carbon atoms and having a carbon-carbon double bond at the terminal carbon atom, such as 1-propylene, 1-butene, 1-hexene, and 1-octene. Only one type of α-olefin in component (A3) may be copolymerized with ethylene, or two or more types may be copolymerized with ethylene.

[0049] The ethylene-α-olefin copolymer block of component (A3) may be exemplified by those having 1-propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene units, etc. as α-olefins as structural units in addition to ethylene units. Preferably, it is derived from an α-olefin having 4 to 8 carbon atoms and having a carbon-carbon double bond at the terminal carbon atom, such as 1-propylene, 1-butene, 1-hexene, or 1-octene. The α-olefin in component (A3) may be one type copolymerized with ethylene, or two or more types may be copolymerized with ethylene. Also, component (A3) may be used alone or in combination of two or more types.

[0050] The content of ethylene units in component (A3) is preferably 50% by weight or more and less than 90% by weight, and more preferably 50% by weight or more and 80% by weight or less, based on the total amount of the content of ethylene units and the content of α-olefin units. The content of ethylene units in component (A3) is preferably high in order to improve the high-temperature impact resistance of component (A3), and low in order to improve the low-temperature impact resistance. The content of ethylene units in component (A3) is more preferably 80% by weight or less. The content of ethylene units is more preferably 70% by weight or less. The content of structural units derived from ethylene and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the crystalline ethylene copolymer (A3) can be determined by nuclear magnetic resonance spectroscopy (NMR).

[0051] The ethylene-α-olefin copolymer, which is the crystalline ethylene copolymer (A3), may have other structural units such as structural units based on a non-conjugated diene (non-conjugated diene unit) in addition to ethylene units and α-olefin units having 3 to 8 carbon atoms. Examples of the non-conjugated diene include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene; and cyclic non-conjugated dienes such as cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, and 6-chloromethyl-5-isopropenyl-2-norbornene. Preferred are 5-ethylidene-2-norbornene and dicyclopentadiene.

[0052] In addition, when the crystalline ethylene copolymer (A3) has other structural units such as non-conjugated diene units, the content thereof is usually 10% by weight or less, preferably 5% by weight or less, based on the entire crystalline ethylene copolymer (A3). The content of the non-conjugated diene units or propylene units can be determined by infrared spectroscopy.

[0053] Specific examples of the crystalline ethylene copolymer (A3) used in this embodiment include block copolymers containing a crystalline ethylene polymer block and an ethylene-α-olefin copolymer block such as an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer, an ethylene-1-octene copolymer, an ethylene-propylene-1-butene copolymer, an ethylene-propylene-1-hexene copolymer, and an ethylene-propylene-1-octene copolymer. These may be used alone or in combination of two or more. Among these, the crystalline ethylene copolymer (A3) is most preferably a block copolymer containing an ethylene polymer block and an ethylene-1-octene copolymer block, i.e., the crystalline ethylene copolymer (A3) is most preferably an olefin block copolymer containing a polymer made of ethylene and an ethylene-1-octene copolymer block.

[0054] The crystalline ethylene copolymer (A3) has a polymer block made of crystalline ethylene, and also has amorphousness due to the ethylene-α-olefin copolymer block. This amorphousness is expressed by the glass transition temperature, and the glass transition temperature measured by the DSC method is preferably -80°C or higher, more preferably -75°C or higher, and on the other hand, is preferably -50°C or lower, more preferably -60°C or lower.

[0055] The melt flow rate (measurement temperature 190 ° C., measurement load 21.18N) of the crystalline ethylene copolymer (A3) is not limited, but is usually 10g / 10 minutes or less, and from the viewpoint of strength, it is preferably 8g / 10 minutes or less, more preferably 5g / 10 minutes or less, and even more preferably 3g / 10 minutes or less. The melt flow rate of the crystalline ethylene copolymer (A3) is usually 0.01g / 10 minutes or more, and from the viewpoint of fluidity, it is preferably 0.05g / 10 minutes or more, and even more preferably 0.10g / 10 minutes or more. The melt flow rate of the component (B) is measured according to ASTM D1238 under the conditions of a measurement temperature of 190 ° C. and a measurement load of 21.18N.

[0056] The density of the crystalline ethylene copolymer (A3) is preferably 0.880 g / cm from the viewpoint of low-temperature impact resistance. 3 More preferably, it is 0.870 g / cm or less. 3 On the other hand, the lower limit is not particularly limited, but is usually 0.850 g / cm 3 That's all.

[0057] The crystalline ethylene copolymer (A3) can be synthesized according to the methods disclosed in JP 2007-529617 A, JP 2008-537563 A, and JP 2008-543978 A. For example, the crystalline ethylene copolymer (A3) can be produced by preparing a composition containing a mixture or reaction product obtained by combining a first olefin polymerization catalyst, a second olefin polymerization catalyst capable of preparing a polymer having different chemical or physical properties from the polymer prepared by the first olefin polymerization catalyst under the same polymerization conditions, and a chain shuttling agent, and contacting the composition with the ethylene and α-olefin under addition polymerization conditions.

[0058] The polymerization of crystalline ethylene copolymer (A3) is preferably carried out by continuous solution polymerization.In the continuous solution polymerization, catalyst components, chain shuttling agent, monomers, and optionally solvent, auxiliary agent, scavenger and polymerization aid are continuously fed into reaction zone, and polymer product is continuously taken out from there.In addition, the length of block can be changed by controlling the ratio and type of catalyst, the ratio and type of chain shuttling agent, polymerization temperature, etc.

[0059] Other conditions for the synthesis of block copolymers are disclosed in Japanese Patent Publication Nos. 2007-529617, 2008-537563, and 2008-543978. Commercially available products include those from Dow Chemical Co., Ltd. Engage (registered trademark)-XLT series and INFUSE (registered trademark) series manufactured by Examples include:

[0060] Propylene-based polymer component (B) The propylene-based polymer component (B) constituting the thermoplastic elastomer composition of this embodiment is a (co)polymer having a content of structural units derived from propylene of more than 50% by weight and not more than 100% by weight. Examples of the propylene-based polymer component (B) include a propylene homopolymer, a propylene random copolymer, and a propylene polymerization material as described below. The propylene-based polymer component (B) may be composed of only one type of propylene-based polymer, or may contain two or more types of propylene-based polymers.

[0061] Examples of the propylene random copolymer include (1) A propylene-ethylene random copolymer having a content of structural units derived from propylene of 90% by weight or more and 99.5% by weight or less and a content of structural units derived from ethylene of 0.5% by weight or more and 10% by weight or less (wherein the total content of structural units derived from propylene and structural units derived from ethylene is 100% by weight); (2) A propylene-ethylene-α-olefin random copolymer having a content of structural units derived from propylene of 81% by weight or more and 99% by weight or less, a content of structural units derived from ethylene of 0.5% by weight or more and 9.5% by weight or less, and a content of structural units derived from α-olefins having 4 to 10 carbon atoms of 0.5% by weight or more and 9.5% by weight or less (wherein the total content of structural units derived from propylene, structural units derived from ethylene, and structural units derived from α-olefins having 4 to 10 carbon atoms is 100% by weight); and (3) A propylene-α-olefin random copolymer having a content of structural units derived from propylene of 90% by weight or more and 99.5% by weight or less and a content of structural units derived from an α-olefin having 4 to 10 carbon atoms of 0.5% by weight or more and 10% by weight or less (wherein the total content of structural units derived from propylene and structural units derived from an α-olefin having 4 to 10 carbon atoms is 100% by weight).

[0062] Examples of the α-olefin having 4 to 10 carbon atoms in the propylene-ethylene-α-olefin random copolymer and the propylene-α-olefin random copolymer include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene.

[0063] Examples of the method for producing the propylene homopolymer and the propylene random copolymer include known polymerization methods using known olefin polymerization catalysts, such as a slurry polymerization method, a solution polymerization method, a bulk polymerization method, and a gas phase polymerization method using a complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, or a nonmetallocene complex. The propylene homopolymer may be produced in one polymerization reactor, or may be produced by multi-stage polymerization in a production facility in which a plurality of reactors are connected in series. When the propylene homopolymer is produced by multi-stage polymerization, the intrinsic viscosity of the propylene homopolymer produced in the first stage and the propylene homopolymer produced in the second stage may be the same or different.

[0064] The propylene polymerization material is a polymerization material consisting of a propylene homopolymer portion (I) and an ethylene copolymer portion (II) having a constitutional unit derived from at least one selected from the group consisting of propylene and an α-olefin having 4 or more carbon atoms, and a constitutional unit derived from ethylene. The content of the propylene homopolymer portion (I) in the propylene polymerization material is 70% by weight to 95% by weight, and the content of the ethylene copolymer portion (II) is 5% by weight to 30% by weight. From the viewpoint of low-temperature impact resistance of a molded product, the content of the propylene homopolymer portion (I) in the propylene polymerization material is preferably 75% by weight to 95% by weight, and the content of the ethylene copolymer portion (II) is 5% by weight to 25% by weight (wherein the total amount of the propylene polymerization material is 100% by weight).

[0065] Examples of the α-olefin having 4 or more carbon atoms in the ethylene copolymer portion (II) include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene. As the α-olefin having 4 or more carbon atoms, an α-olefin having 4 to 20 carbon atoms is preferable, an α-olefin having 4 to 10 carbon atoms is more preferable, and 1-butene, 1-hexene, or 1-octene is even more preferable. The α-olefins having 4 or more carbon atoms may be used alone or in combination of two or more kinds.

[0066] The content of the structural unit derived from ethylene in the ethylene copolymer portion (II) is usually 22% by weight or more and 80% by weight or less, preferably 25% by weight or more and 70% by weight or less, more preferably 27% by weight or more and 60% by weight or less, from the viewpoint of low-temperature impact resistance of the molded article. The content of the structural unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the ethylene copolymer portion (II) is usually 20% by weight or more and 78% by weight or less, preferably 30% by weight or more and 75% by weight or less, more preferably 40% by weight or more and 73% by weight or less, from the viewpoint of low-temperature impact resistance of the molded article (however, the total content of the structural unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms and the structural unit derived from ethylene is 100% by weight). The content of the structural unit derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms and the content of the structural unit derived from ethylene can be determined by infrared spectroscopy.

[0067] Examples of the ethylene copolymer portion (II) include propylene-ethylene copolymer, ethylene-(1-butene) copolymer, ethylene-(1-hexene) copolymer, ethylene-(1-octene) copolymer, propylene-ethylene-(1-butene) copolymer, propylene-ethylene-(1-hexene) copolymer, propylene-ethylene-(1-octene) copolymer, etc., and propylene-ethylene copolymer or propylene-ethylene-(1-butene) copolymer is preferred.The ethylene copolymer portion (II) may be a random copolymer or a block copolymer.

[0068] The intrinsic viscosity (hereinafter, [η cxs From the viewpoint of low-temperature impact resistance of the molded product, the viscosity of the polymer is preferably 2.0 dl / g or more and 8.0 dl / g or less, and more preferably 2.2 dl / g or more and 7.0 dl / g or less. It is more preferable to use a 20°C xylene insoluble portion (hereinafter referred to as the CXIS portion) having an intrinsic viscosity (hereinafter referred to as [η cxis ]) for [η cxs The ratio of [Ratio of] is preferably 2.0 or more and 12.0 or less. The intrinsic viscosity is determined by the following procedure. The reduced viscosity is measured in tetralin at 135°C using an Ubbelohde viscometer, and the intrinsic viscosity is calculated from the reduced viscosity obtained by extrapolation according to the calculation method described on page 491 of "Polymer Solutions, Polymer Experiments 11" (published by Kyoritsu Shuppan Co., Ltd. in 1982). Here, the CXS and CXIS fractions are obtained by the following method. Approximately 5 g of propylene polymerization material is completely dissolved in 500 ml of boiling xylene. The resulting xylene solution is gradually cooled to 20°C, and conditioned at 20°C for 4 hours or more, and the precipitate and the solution are separated by filtration. The precipitate is the CXIS fraction, and the product obtained by removing the solvent from the solution is the CXS fraction.

[0069] The propylene polymerization material can be produced by multi-stage polymerization using a polymerization catalyst. For example, the propylene polymerization material can be produced by producing a propylene homopolymer portion (I) in a first polymerization step and producing an ethylene copolymer portion (II) in a second polymerization step. Examples of the polymerization catalyst used in the production of the propylene polymerization material include a Ziegler type catalyst system, a Ziegler-Natta type catalyst system, a catalyst system consisting of a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl ring and an alkylaluminoxane, a catalyst system consisting of a transition metal compound of Group 4 of the periodic table having a cyclopentadienyl ring, a compound that reacts with the transition metal compound to form an ionic complex, and an organoaluminum compound, and the like. In addition, a prepolymerization catalyst may be used in the presence of the above-mentioned polymerization catalyst. Examples of the prepolymerization catalyst include the catalyst systems described in JP-A-61-218606, JP-A-61-287904, JP-A-5-194685, JP-A-7-216017, JP-A-9-316147, JP-A-10-212319, and JP-A-2004-182981.

[0070] Examples of the polymerization method in the production of the propylene polymerization material include bulk polymerization, solution polymerization, slurry polymerization, and gas phase polymerization. Examples of the inert hydrocarbon solvent used in the solution polymerization and slurry polymerization include propane, butane, isobutane, pentane, hexane, heptane, and octane. Two or more of these polymerization methods may be combined, and may be either batch or continuous. Examples of the polymerization method in the production of the propylene polymerization material include continuous gas phase polymerization and bulk-gas phase polymerization in which bulk polymerization and gas phase polymerization are performed continuously.

[0071] The melt flow rate of the propylene polymer component (B), measured in accordance with JIS K7210 at 230°C under a load of 21.18 N, is usually from 10 g / 10 min to 300 g / 10 min, and from the viewpoint of the tensile strength of the molded product, preferably from 10 g / 10 min to 100 g / 10 min.

[0072] The isotactic pentad fraction of the propylene polymer component (B) measured by 13C-NMR is preferably 0.95 or more, more preferably 0.98 or more. Here, the isotactic pentad fraction is the fraction of propylene monomer units at the center of an isotactic chain in the pentad unit of the molecular chain of the propylene polymer resin, in other words, the fraction of propylene monomer units in a chain in which five consecutive propylene monomer units are meso-bonded (hereinafter referred to as mmmm). The method for measuring the isotactic pentad fraction is the method described by A. Zambelli et al. in Macromolecules, 6, 925 (1973), that is, the method measured by 13C-NMR.

[0073] Specifically, the ratio of the area of ​​the NMR peaks assigned to mmmm to the area of ​​the absorption peaks in the methyl carbon region measured by 13C-NMR spectroscopy is the isotactic pentad fraction.

[0074] The melting temperature of the propylene-based polymer component (B) is usually 100°C or higher. The melting temperature of the propylene homopolymer and propylene polymer material, which are preferred forms of the propylene-based polymer component (B), is preferably 155°C or higher, more preferably 160°C or higher. The melting temperature of the propylene random copolymer, which is preferred forms of the propylene-based polymer component (B), is preferably 130°C or higher, more preferably 135°C or higher. The melting temperature of the propylene-based polymer component (B) is usually 175°C or lower. In the present invention, the melting temperature is the peak temperature of the endothermic peak with the largest peak temperature in the differential scanning calorimeter curve during the temperature increase operation measured by the differential scanning calorimeter. The measurement conditions of the differential scanning calorimeter curve are as follows.

[0075] <Measurement conditions> Temperature-reducing operation: The propylene polymer component (B) is melted at 220° C., and then the temperature is reduced from 220° C. to −80° C. at a rate of 10° C. / min. Temperature increase operation: After lowering the temperature from 220°C to -80°C, immediately increase the temperature from -80°C to 220°C at a rate of 10°C / min.

[0076] Propylene polymer (B2) In this embodiment, the propylene-based polymer component (B) has an intrinsic viscosity [η cxis In the case where the propylene polymer (B2) is a propylene homopolymer produced by multistage polymerization, the intrinsic viscosity [η cxis ] is preferably 1.5 dl / g or more and 7.5 dl / g or less. Intrinsic viscosity [η] of the CXIS part of the propylene polymer (B2) cxis The method for measuring the intrinsic viscosity [η cxis The measurement method for is the same as that described above in detail. Intrinsic viscosity [η] of the CXIS part of the propylene polymer (B2) cxis In one embodiment, the intrinsic viscosity [η cxis ] is preferably 1.5 dl / g or more and 6.0 dl / g or less. The content of the propylene polymer (B2) in the propylene polymer component (B) is not particularly limited, but is preferably from 1 wt % to 50 wt % (wherein the total weight of the propylene polymer component (B) is taken as 100 wt %), and particularly preferably from 5 wt % to 20 wt %. In addition, a substance which corresponds to the propylene polymer component (B) but does not correspond to the propylene polymer (B2) is also called a propylene polymer (B1).

[0077] Other Ingredients The thermoplastic elastomer composition of the present invention may contain various additives in addition to the resin components that normally constitute a thermoplastic elastomer composition. The thermoplastic elastomer composition of each of the above embodiments may contain various additives in addition to the ethylene polymer component (A) and the propylene polymer component (B). Examples of additives include polymers or oligomers other than the above components (A) and (B), softeners such as mineral oil, inorganic fillers (talc, calcium carbonate, calcined kaolin, glass fiber, hollow glass spheres, silica, metal soap, titanium dioxide, mica, potassium titanate fiber, etc.), organic fillers (fibers, wood flour, cellulose powder, carbon fiber, carbon black, etc.), lubricants (silicone oil, silicone gum, etc.), antioxidants (phenol-based, sulfur-based, phosphorus-based, lactone-based, vitamin-based, etc.), weathering stabilizers, ultraviolet absorbers (benzotriazole-based, triazine-based, anilide-based, benzophenone-based, etc.), heat stabilizers, light stabilizers (hinder The composition may contain, for example, amine-based, benzoate-based, pigments (inorganic pigments, organic pigments, pigment dispersants, etc.), nucleating agents, foaming agents, foam nucleating agents, plasticizers, flame retardants, brighteners, antibacterial agents, light diffusing agents, adsorbents (metal oxides (zinc oxide, magnesium oxide, etc.), wetting and dispersing agents, VOC / odor stripping agents, water storage agents (aqueous media containing amphiphilic polymers, etc.), scratch resistance improvers, metal chlorides (iron chloride, calcium chloride, etc.), hydrotalcite, aluminates, etc.), crosslinking agents (organic peroxides, etc.), crosslinking assistants (trimethylolpropane trimethacrylate, N,N'm-phenylene bismaleimide, divinylbenzene, silane coupling agents, etc.). These additives may be used alone or in combination of two or more.

[0078] Examples of resins other than component (A) and component (B) include olefin-based resins (excluding those corresponding to component (A) and component (B)), olefin-based elastomers (excluding those corresponding to component (A) and component (B)), (C) hydrogenated products of block copolymers containing a polymer block of a monovinyl-substituted aromatic hydrocarbon compound and a polymer block of a conjugated diene compound, polyphenylene ether-based resins, polyamide-based resins, polyester-based resins, polyoxymethylene-based resins, polymethyl methacrylate-based resins, and the like. Olefin-based resins include, for example, functionalized ethylene-based polymers such as ethylene vinyl acetate ("EVA"), polymers having maleic anhydride grafted to polyolefins such as polypropylene, ethylene acrylate copolymers such as ethylene methyl acrylate ("EMA"), metallocene polypropylene olefin block copolymers, and the like. Metallocene polypropylene olefin block copolymers are polypropylenes with alternating crystalline hard "blocks" and amorphous soft "blocks" that are not randomly distributed (i.e., the block sequence is controlled). An example of a metallocene polypropylene olefin block copolymer includes, but is not limited to, INTUNE (registered trademark, manufactured by The Dow Chemical Company). An example of an olefin-based elastomer is a copolymer comprising a structural unit derived from ethylene and a structural unit derived from at least one selected from the group consisting of propylene and an α-olefin having 4 to 12 carbon atoms. Examples of copolymers consisting of a structural unit derived from ethylene and a structural unit derived from at least one selected from the group consisting of propylene and an α-olefin having 4 to 12 carbon atoms include propylene-ethylene copolymers, ethylene-1-butene copolymers, propylene-ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene-1-octene copolymers, propylene-ethylene-1-hexene copolymers, propylene-ethylene-1-octene copolymers, ethylene-1-butene-1-octene copolymers, and the like, and propylene-ethylene copolymers or ethylene-1-octene copolymers, propylene-ethylene-1-butene copolymers, propylene-ethylene-1-hexene copolymers, propylene-ethylene-1-octene copolymers, ethylene-1-octene copolymers, and ethylene-1-butene-1-octene copolymers are preferred. The copolymer comprising a structural unit derived from ethylene and a structural unit derived from at least one selected from the group consisting of propylene and an α-olefin having 4 to 12 carbon atoms may be a random copolymer or a block copolymer. Examples of the block copolymer include an olefin-based block copolymer comprising a polymerization block of ethylene and an ethylene-α-olefin copolymer block.

[0079] The softener may be a mineral oil such as paraffinic mineral oil, naphthenic mineral oil, or aromatic mineral oil, and is preferably paraffinic mineral oil. The softener may be added when component (A) and component (B) are melt-kneaded, or any of the components may be mixed with the softener before the melt-kneading. Examples of the method for mixing the ethylene copolymer and the softener include (1) a method in which a solid ethylene copolymer and a softener are mixed in a mixer, and (2) a method in which a solution of the ethylene copolymer and a softener are mixed to produce a mixture, and then the solvent in the mixture is removed. The content of the softener is preferably 0.1% by weight or more and 15% by weight or less, with the total amount of the thermoplastic elastomer composition being 100% by weight. In this specification, the term "mineral oil" means a substance that is liquid or greasy at room temperature and is obtained from petroleum-derived hydrocarbon compounds and is composed of at least one compound selected from the group consisting of aromatic compounds, naphthenic compounds, and paraffinic compounds.

[0080] The (C) hydrogenated block copolymer containing a polymer block of a monovinyl-substituted aromatic hydrocarbon compound and a polymer block of a conjugated diene compound is a hydrogenated product obtained by hydrogenating the Y portion of a block copolymer represented by the following formula (1) or formula (2). XY formula (1) X(-YX)n Formula (2) (In the formula, X represents a polymer block of a monovinyl-substituted aromatic hydrocarbon, Y represents a conjugated diene polymer block, and n represents an integer of 1 to 5, preferably 1 or 2.) The content of the monovinyl-substituted aromatic hydrocarbon compound is preferably 0.1% by weight or more and 60% by weight or less, more preferably 5% by weight or more and 40% by weight or less, and particularly preferably 5% by weight or more and 20% by weight or less, based on 100% by weight of the total amount of the thermoplastic elastomer composition.

[0081] The monovinyl-substituted aromatic hydrocarbon constituting the polymer block represented by X in the formula (1) or (2) includes styrene or its derivatives, such as styrene, α-methylstyrene, p-methylstyrene, chlorostyrene, lower alkyl-substituted styrene, vinylnaphthalene, etc. These monovinyl-substituted aromatic hydrocarbons may be used alone or in combination of at least two kinds. Styrene is preferred.

[0082] Examples of the conjugated diene constituting the polymer block represented by Y in the formula (1) or (2) include butadiene, isoprene, chloroprene, etc. These may be used alone or in combination of at least two kinds. Preferred is butadiene or isoprene. When butadiene is used as the conjugated diene, the proportion of 1,2-bonds in the polybutadiene block is usually 20 to 80% by weight, and preferably 30 to 60% by weight.

[0083] In the hydrogenated product of the block copolymer represented by the formula (1) or (2), the hydrogenation rate of the conjugated diene polymer block (Y part) is usually 90 mol% or more, preferably 95 mol% or more (where the total amount of the Y part is 100 mol%). The content of the X part is usually 1 to 30 wt% and preferably 10 to 25 wt% (where the total amount of the hydrogenated product of the block copolymer represented by the formula (1) or (2) is 100 wt%). The melt flow rate (MFR, ASTM D-1238, 230°C, 2.16 kg load) of the hydrogenated block copolymer represented by the formula (1) or (2) is usually preferably 30 g / 10 min or less, more preferably 1 to 10 g / 10 min.

[0084] The hydrogenated product of the block copolymer represented by the formula (1) or (2) includes a styrene-based block copolymer obtained by hydrogenation. For example, styrene-ethylene-butene-styrene block copolymer (SEBS) is obtained by hydrogenating styrene-butadiene-styrene triblock copolymer, styrene-ethylene-propylene-styrene block copolymer (SEPS) is obtained by hydrogenating styrene-isoprene-styrene triblock copolymer, and styrene-ethylene-propylene block copolymer (SEP) is obtained by hydrogenating styrene-isoprene diblock copolymer.

[0085] Examples of the method for producing the block copolymer before hydrogenation include a method for performing block copolymerization of each monomer in an inert solvent in the presence of a lithium catalyst or a Ziegler catalyst, etc. Examples of the detailed production method include the production method described in JP-B-40-23798 and the like.

[0086] The method of hydrogenating the block copolymer represented by the formula (1) or (2) may be, for example, a method of hydrogenating the block copolymer in an inert solvent in the presence of a known hydrogenation catalyst, and the detailed method is described in, for example, JP-B-42-8704, JP-B-43-6636, JP-B-46-20814, etc.

[0087] The hydrogenated block copolymer represented by the formula (1) or (2) may be a commercially available product, such as Kraton G1657 (Kraton Polymers Japan, Ltd., registered trademark), Septon 2004 (Kuraray Co., Ltd., registered trademark), Tuftec H1052, and Tuftec H1062 (Asahi Kasei Chemicals Corporation, registered trademark).

[0088] Production of Thermoplastic Elastomer Composition The thermoplastic elastomer composition can be produced by kneading the raw material resins, for example, the ethylene-based polymer component (A) and the propylene-based polymer component (B), and various additives as desired, in a conventional manner using a conventional extruder, Banbury mixer, roll, Brabender Plastograph, Kneader Brabender, etc. It is preferable to produce the composition using an extruder, particularly a twin-screw extruder. In producing the thermoplastic elastomer composition of the present invention, crosslinking may be carried out or it may not be crosslinked. From the viewpoints of flowability and moldability into thin-walled shapes, etc., the non-crosslinked form is preferred. When crosslinking is carried out, it is preferred that various crosslinking agents and crosslinking assistants are introduced into an extruder, particularly a twin-screw extruder, in addition to the raw resin, and crosslinking is carried out by dynamic heat treatment. Furthermore, in the case where crosslinking is performed and the thermoplastic elastomer composition contains the component (B2), the thermoplastic elastomer composition is preferably produced by a production method including a step of dynamically heat-treating the ethylene-based polymer component (A) and the propylene-based polymer component (B) in the presence of a crosslinking agent to crosslink them and obtain a thermoplastic elastomer precursor, and a step of kneading the thermoplastic elastomer precursor and the component (B2) to obtain a thermoplastic elastomer composition.

[0089] The thermoplastic elastomer composition of the present invention is used in various applications, and is particularly suitable for applications requiring impact resistance, particularly both low-temperature impact resistance and high-temperature impact resistance, such as, but not limited to, automobile parts, industrial machine parts, electronic / electrical device parts, building materials, etc.

[0090] Among these, it is particularly suitable for use in automobile interior parts which have a wide operating temperature range, and in particular for use as airbag storage covers which require strict control of impact resistance. In this embodiment, the thermoplastic elastomer composition of the present invention can be used to mold an airbag storage cover by, for example, a normal injection molding method, or, if necessary, by various molding methods such as gas injection molding, injection compression molding, short shot foam molding, etc. The molding conditions for the above-mentioned injection molding are generally a molding temperature of 100 to 300°C, preferably 150 to 280°C, an injection pressure of 5 to 100 MPa, preferably 10 to 80 MPa, and a mold temperature of 20 to 80°C, preferably 20 to 60°C. EXAMPLES

[0091] The present invention will be described in more detail below with reference to examples and comparative examples. Note that the technical scope of the present invention is not limited in any way by these examples.

[0092] The physical properties in the examples and comparative examples were evaluated by the following methods.

[0093] [Measurement of physical properties] 1.Melt Flow Rate (MFR) The melt flow rate was measured by the method B in accordance with JIS K7210 under conditions of 230° C. and a load of 21.18 N.

[0094] 2. Enthalpy of fusion ΔH m1 and ΔH m2 Melting enthalpy ΔH in the temperature ranges of 70°C to 200°C and 70°C to 140°Cm1 and ΔH m2 was calculated as the heat of fusion by analyzing the portions of the melting curve measured by differential scanning calorimetry within the temperature ranges of 70°C to 200°C and 70°C to 140°C in accordance with a method in accordance with JIS K7122-1987. The melting temperatures within the temperature ranges of 70°C to 200°C and 70°C to 140°C were determined as the temperatures of the apexes of the melting peaks obtained by analyzing the melting curve measured by differential scanning calorimetry in the temperature ranges of 70°C to 200°C and 70°C to 140°C according to a method in accordance with JIS K7121-1987. The glass transition temperature was determined as the midpoint glass transition temperature obtained by analyzing a melting curve measured by differential scanning calorimetry as described below according to a method in accordance with JIS K7121-1987. In the differential scanning calorimeter curve during the temperature increase operation, the peak temperature of the largest endothermic peak was taken as the melting temperature. <Measurement conditions> The sample is melted at 220° C. and then cooled from 220° C. to −80° C. at a rate of 10° C. / min. Temperature increase operation: After lowering the temperature from 220°C to -80°C, immediately increase the temperature from -80°C to 220°C at a rate of 10°C / min.

[0095] 3. Intrinsic viscosity ([η cxs ],[η cxis ], unit: dl / g) After completely dissolving about 5 g of the sample in 500 ml of boiling xylene, the xylene solution was gradually cooled to 20°C and conditioned at 20°C for 4 hours or more, after which the precipitate and the solution were separated by filtration. The precipitate was designated as the CXIS portion, and the material obtained by removing the solvent from the solution was designated as the CXS portion. The reduced viscosity was measured in tetralin at 135° C. using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the reduced viscosity obtained by extrapolation according to the calculation method described on page 491 of “Polymer Solutions, Polymer Experiments 11” (published by Kyoritsu Shuppan Co., Ltd. in 1982).

[0096] 4. Isotactic pentad fraction Measurements were performed by nuclear magnetic resonance spectroscopy (NMR) under the following conditions (1) to (7). The isotactic pentad fraction was calculated by calculating the ratio of the area of ​​the NMR peaks attributable to mmmm to the area of ​​the NMR peaks in the methyl carbon region according to the method described in the literature (Macromolecules, 6, 925 (1973)). (1) Equipment: BRUKER AvanceIII HD600 (10mm cryoprobe) (2) Measurement solvent: 1,2-dichlorobenzene-d4 / 1,2-dichlorobenzene (20 / 80 volume ratio) (3) Measurement temperature: 130℃ (4) Measurement method: Proton decoupling method (5) Pulse width: 45 degrees (6) Pulse repetition time: 4 seconds (7) Chemical shift value standard: tetramethylsilane

[0097] 5. The content of constituent units derived from ethylene and the content of constituent units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms in the non-conjugated diene copolymer of component (A) The non-conjugated diene copolymer was molded into a film having a thickness of about 0.1 mm using a hot press machine, and the infrared absorption spectrum of the film was measured using an infrared spectrophotometer (IR-810 manufactured by JASCO Corporation). From the infrared absorption spectrum, the content of structural units derived from ethylene in the non-conjugated diene copolymer and the content of structural units derived from at least one selected from the group consisting of propylene and α-olefins having 4 or more carbon atoms were determined according to the method described in the literature (Characterization of Polyethylene by Infrared Absorption Spectroscopy, by Takayama, Usami, et al., or Die Makromolekulare Chemie, 177, 461 (1976) by Mc Rae, MA, Madam S, WF, et al.).

[0098] 6. Iodine value of non-conjugated diene copolymer of component (A) The non-conjugated diene copolymer was formed into a film having a thickness of about 0.5 mm using a hot press machine. The peak (1611 cm) derived from dicyclopentadiene of the film was detected by infrared spectroscopy. -1 absorption peak) and the peak due to 5-ethylidene-2-norbornene (1688 cm -1 The intensity of the absorption peak of the double bond was measured. The molar content of the double bond was calculated from the peak intensity, and the iodine value was calculated from the molar content.

[0099] 7.Molecular weight distribution The weight average molecular weight (Mw) and number average molecular weight (Mn) were measured by gel permeation chromatography (GPC) under the following conditions (1) to (9), and the molecular weight distribution (Mw / Mn) was calculated. (1) Instrument: Tosoh HLC-8121 GPC / HT (2) Separation column: 3 columns of GMHHR-H(S)HT manufactured by Tosoh (3) Measurement temperature: 140℃ (4) Carrier: o-dichlorobenzene (5)Flow rate: 1.0mL / min (6) Sample concentration: Approximately 1 mg / mL (7) Sample injection volume: 400 μL (8) Detector: Differential refraction (9) Molecular weight standard: standard polystyrene

[0100] 8.Mooney Viscosity Mooney viscosity was measured at 125°C according to ASTM D-1646.

[0101] 9. Density (unit: g / cm 3 ) The density was measured without annealing according to JIS K7112.

[0102] 10. Content of structural units derived from ethylene in the ethylene copolymers of components (A), (B) and (C) (unit: weight %) Measurements were carried out by nuclear magnetic resonance spectroscopy (NMR) under the following conditions (1) to (7), and the content of structural units derived from ethylene in the ethylene copolymer was determined according to the method described in the literature (JMS-REV. MACROMOL. CHEM. PHYS., C29, 201-317 (1989)) (wherein the total amount of the ethylene copolymer was taken as 100% by weight). (1) Equipment: BRUKER AvanceIII HD600 (10mm cryoprobe) (2) Measurement solvent: 1,1,2,2-tetrachloroethane-d2 / 1,2-dichlorobenzene (15 / 85 volume ratio) (3) Measurement temperature: 135℃ (4) Measurement method: Proton decoupling method (5) Pulse width: 45 degrees (6) Pulse repetition time: 4 seconds (7) Chemical shift value standard: tetramethylsilane

[0103] 11. Manufacturing method of injection molded body A Toshiba Machine EC160NII injection molding machine was used, with a side gate flat mold, cylinder temperature 220°C, mold temperature 50°C, and injection rate 25cm 3 The thermoplastic elastomer compositions of the Examples and Comparative Examples were injection molded under conditions of 1000 g / sec to obtain injection molded articles having a length of 90 mm, a width of 150 mm and a thickness of 2.0 mm.

[0104] 12. How to prepare test specimens The center of the injection molded product produced in 11 above was punched out using a dumbbell cutter (30 x 30 mm) manufactured by Dumbbell Co., Ltd. to obtain a test specimen measuring 30 mm (width) x 30 mm (length) x 2.0 mm (thickness).

[0105] 13.Low temperature impact resistance (IZOD impact strength) The impact resistance of the injection molded article produced in the above item 11 was measured in accordance with JIS K7110. The measurement was carried out at -40°C. The measurement results were judged as follows: P (Partial fracture): Does not meet the definition of hinge fracture, incomplete fracture H (hinge fracture): Incomplete fracture where only a thin hinge-like surface layer, which has lost its bending stiffness, remains as a single piece and does not separate. C (Complete failure): The test specimen breaks into two or more pieces.

[0106] 14.High temperature impact resistance (IZOD impact strength) The impact resistance of the injection molded article produced in the above item 11 was measured in accordance with JIS K7110. The measurement was carried out at 85°C.

[0107] 15.Solvent swelling In accordance with JIS K6258, the test piece prepared in 12. above was immersed in petroleum benzine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) at 23°C for 24 hours, after which the width, length and thickness of the test piece were measured, and the area increase rate and volume increase rate were calculated using the following formulas. Area increase rate S: (S 24 / S0-1)×100 [%] Volume increase rate V:(V 24 / V0-1)×100 [%] (S0: area before impregnation with petroleum benzine (width x length), S 24 : Area after petroleum benzine impregnation (width × length), V0: Volume before petroleum benzine impregnation (width × length × thickness), V 24 : Volume after soaking in petroleum benzine (width x length x thickness)

[0108] [Raw materials] Details of the starting materials used in the Examples / Comparative Examples are as follows:

[0109] <Ethylene-based polymer component (A)> (A1-1-i) Ethylene-1-octene copolymer Dow Chemical Company, Engage 8842 The melting enthalpy observed in the temperature range of 70°C to 140°C by differential scanning calorimetry is 0 J / g, the content of structural units derived from ethylene is 55% by weight, the content of structural units derived from 1-octene is 45% by weight, and the Mooney viscosity (ML 1+4 ,125℃)=23, density=0.857g / cm3

[0110] (A1-2-i) Ethylene-propylene-5-ethylidene-2-norbornene copolymer Preparation method Hexane was fed to the first stainless steel polymerization tank equipped with an agitator at a rate of 408 g / (hr·L), ethylene and propylene at a rate of 25.4 g / (hr·L) and 117.7 g / (hr·L) per unit time and unit volume of the polymerization tank. VOCl3 and ethanol were mixed and stirred in a line mixer at a rate of 26.5 mg / (hr·L) and 12.7 mg / (hr·L) (VOCl3 / ethanol = 1 / 1.8 (molar ratio)) and then fed to the polymerization tank. Ethyl aluminum sesquichloride (EASC) and hydrogen were fed to the polymerization tank at a rate of 158.7 mg / (hr·L) and 0.05 NL / (hr·L), respectively. 5-ethylidene-2-norbornene was further fed to the polymerization tank at a rate of 0.5 g / (hr·L). The temperature of the polymerization tank was kept at 41°C. In the polymerization tank, 38 g / (hr·L) of non-conjugated diene copolymer was produced per unit time and unit volume of the polymerization tank. The polymerization solution extracted from the first polymerization tank was then fed to a second polymerization tank made of stainless steel and having the same volume as the first polymerization tank, equipped with a stirrer. Hexane was fed at a rate of 204 g / (hr·L), ethylene and propylene at a rate of 15.2 g / (hr·L) and 100.4 g / (hr·L), respectively, per unit time and unit volume of the polymerization tank. VOCl3 and ethanol were mixed and stirred in a line mixer at a rate of 16.7 mg / (hr·L) and 8.0 mg / (hr·L), respectively (VOCl3 / ethanol = 1 / 1.8 (molar ratio)), and then fed to the polymerization tank. Ethyl aluminum sesquichloride (EASC) was also fed to the polymerization tank at a rate of 66.8 mg / (hr·L). The temperature of the polymerization tank was kept at 45°C. In the second polymerization reactor, 19 g / (hr·L) of non-conjugated diene copolymer was produced per unit time and unit reactor volume. The Mooney viscosity (ML 1+4 , 125°C), the content of structural units derived from ethylene, the content of structural units derived from propylene, the iodine value, and the molecular weight distribution are as follows. Mooney Viscosity (ML 1+4 ,125℃)=65, MFR(190℃,21.18N)=0.5g / 10min, content of structural units derived from ethylene=55% by weight, content of structural units derived from propylene=45% by weight, iodine value=2.1, molecular weight distribution=1.9, melting enthalpy observed in the temperature range of 70℃ to 140℃ by differential scanning calorimetry=0 J / g, (A2-1-i) High density polyethylene (HDPE) Product name: "M6901" manufactured by Keiyo Polyethylene Co., Ltd. Melting temperature = 132 ° C., melting enthalpy observed in the temperature range of 70 ° C. to 140 ° C. by differential scanning calorimetry = 236 J / g, MFR(190℃, 21.18N)=13g / 10min, density=0.962g / cm 3 , the content of structural units derived from ethylene=100% by weight (A2-2-i) Low-density polyethylene (LDPE) Sumitomo Chemical Co., Ltd. Product name "G801" Melting temperature = 104 ° C., melting enthalpy observed in the temperature range of 70 ° C. to 140 ° C. by differential scanning calorimetry = 128 J / g, MFR(190℃, 21.18N)=20g / 10min, density=0.919g / cm 3 , the content of structural units derived from ethylene=100% by weight

[0111] (A3-i) Olefin block copolymer (OBC) Dow Chemical Company product name: "Engage XLT8677" Melting temperature = 118 °C, melting enthalpy observed in the temperature range of 70 °C to 140 °C by differential scanning calorimetry = 42 J / g, MFR (190 °C, 21.18 N) = 0.5 g / 10 min, glass transition temperature (DSC method) = -67 °C, density = 0.870 g / cm 3 , the content of structural units derived from ethylene=52% by weight

[0112] (A3-ii) Olefin block copolymer (OBC) Dow Chemical Company product name: "INFUSE D9007" Melting temperature = 119 °C, Melting enthalpy observed in the temperature range of 70 °C to 140 °C by differential scanning calorimetry = 37 J / g, MFR (190 °C, 21.18 N) = 0.5 g / 10 min, glass transition temperature (DSC method) = -63 °C, density = 0.870 g / cm 3 , the content of structural units derived from ethylene=56% by weight

[0113] <Propylene-Based Polymer Component (B)> (B1-1-i) Propylene homopolymer (h-PP) MFR(230℃)=40g / 10min, [η cxis ]=1.25dl / g (B1-2-i) Propylene polymerization material comprising a propylene homopolymer portion (I) and an ethylene copolymer portion (II) Product name: Noblen AZ565, manufactured by Sumitomo Chemical Co., Ltd. MFR(230℃)=32g / 10min, melting temperature=165℃, [η cxis ]=1.0dl / g, [η cxs ]=5.0 dl / g, isotactic pentad fraction=0.98, content of ethylene copolymer portion (II)=16% by weight, content of constitutional units derived from ethylene in the ethylene copolymer portion (II)=35% by weight (B2-i) Propylene homopolymer (h-PP) MFR(230℃)=0.5g / 10min, [η cxis ]=3.0dl / g (B2-ii) Propylene homopolymer (h-PP) B2-ii is a propylene homopolymer produced by multi-stage polymerization. B2-ii is a mixture of a propylene homopolymer component b1 produced in a first stage and a propylene homopolymer component b2 produced in a second stage. The content of the propylene homopolymer component b1 in the first stage was 18% by weight, and the content of the propylene homopolymer component b2 in the second stage was 82% by weight. MFR(230℃)=11g / 10min, melting temperature=165℃, [η cxis ] total= 2.0 dl / g, b1 [η cxis ]=7.0dl / g, b2 [η cxis ]=0.92dl / g

[0114] (C1-i) Styrene-ethylene-butene-styrene block copolymer (SEBS) Asahi Kasei Corporation Product name: "Tuftec H1062" MFR(230℃)=17g / 10min, styrene content=18wt%

[0115] <Other ingredients> Antioxidant: Sumitomo Chemical Co., Ltd. Product name: "Sumilizer GA80" Antioxidant: BASF Japan Ltd. Product name "Irgafos 168"

[0116] <Example 1> A thermoplastic elastomer composition was obtained by melt-kneading 40.0 parts by weight of an ethylene polymer (A1-1-i), 10.0 parts by weight of an ethylene polymer (A2-1-i), 40.0 parts by weight of a propylene polymer (B1-1-i), 10.0 parts by weight of a propylene polymer (B2-i) (wherein the total of component (A) (components beginning with the symbol "(A)". In this embodiment, (A1-1-i) and (A2-1-i)) and component (B) (components beginning with the symbol "(B)". In this embodiment, (B1-1-i) and (B2-i)) is 100 parts by weight).), 0.10 parts by weight of an antioxidant (Sumilizer GA80), and 0.10 parts by weight of an antioxidant (Irgafos 168) were mixed in a twin-screw extruder at a cylinder temperature of 200°C. The obtained thermoplastic elastomer composition was injection molded to obtain a molded article by the method described in 11. The physical properties of the molded article were measured and the results are shown in Table 1.

[0117] <Examples 2 to 14 and Comparative Examples 1 to 4, 6 to 10> A thermoplastic elastomer composition was produced in the same manner as in Example 1, using the components and amounts shown in Table 1 or Table 2. The obtained thermoplastic elastomer composition was injection molded to obtain a molded article by the method described in 11 above. The results of measuring the physical properties of the molded article are shown in Table 1 or Table 2.

[0118] <Comparative Example 5> A thermoplastic elastomer composition was produced in the same manner as in Example 1, using the components and amounts shown in Table 2. When the obtained thermoplastic elastomer composition was injection molded by the method described in 11 above, the molten resin did not spread throughout the entire mold, and only an injection molded article smaller than the mold size was obtained. A test piece was punched out from near the center of the injection molded article by the method described in 12 above, and physical properties were measured. The results are shown in Table 2.

[0119] [Table 1-1]

[0120] [Table 1-2]

[0121] [Table 2] [Industrial Applicability]

[0122] Since the thermoplastic elastomer composition of the present invention can give a molded article having both high levels of low-temperature impact resistance and high-temperature impact resistance, it can be suitably used for producing molded articles to be used in a wide temperature range, such as airbag storage covers, and has high applicability in various industrial fields, such as the automobile and other transportation machinery industry, the sports and leisure goods industry, the household goods industry, the electrical and electronic equipment industry, and the construction industry.

Claims

1. A thermoplastic elastomer composition containing an ethylene-based polymer component (A) and a propylene-based polymer component (B), the thermoplastic elastomer composition being extruded in a cylinder at a temperature of 220°C, a mold at a temperature of 50°C, and an injection rate of 25 cm 3 A molded body was obtained by injection molding into a mold cavity of 90 mm width × 150 mm length × 2.0 mm thickness under the condition of 0.1 μm / sec., and a test piece of 30 mm width × 30 mm length × 2.0 mm thickness was obtained by punching out the vicinity of the center of the molded body. The test piece satisfied the following requirements (1) and (2): Requirement (1): The area increase rate S of the test piece after immersion in petroleum benzine at 23° C. for 24 hours is 20% or less; Requirement (2): The volume increase rate V of the test piece after immersion in petroleum benzine at 23° C. for 24 hours is 20% or more and 125% or less. A thermoplastic elastomer composition, wherein the ethylene-based polymer component (A) contains one or more ethylene-based polymers selected from the group consisting of the following components (A1), (A2), and (A3), and the fusion enthalpy ΔH mA of the ethylene-based polymer component (A) observed within a temperature range of 70° C. or more and 140° C. or less by differential scanning calorimetry is 1 J / g or more and 115 J / g or less: Component (A1): Amorphous ethylene polymer; Component (A2): a crystalline ethylene-based polymer containing 90% by weight or more of structural units derived from ethylene; Component (A3): A crystalline ethylene copolymer in which the content of structural units derived from ethylene is 50% by weight or more and less than 90% by weight.

2. The thermoplastic elastomer composition according to claim 1, wherein the ethylene-based polymer component (A) contains a component (A1), and the melting enthalpy of the component (A1) observed within a temperature range of 70°C or higher and 140°C or lower by differential scanning calorimetry is less than 10 J / g.

3. The fusion enthalpy ΔH observed in the temperature range of 70° C. to 200° C. by differential scanning calorimetry m1 The thermoplastic elastomer composition according to claim 1 or 2, wherein the strength is 115 J / g or less.

4. The fusion enthalpy ΔH observed in the temperature range of 70° C. to 140° C. by differential scanning calorimetry m2 The thermoplastic elastomer composition according to any one of claims 1 to 3, wherein the modulus is 1 J / g or more.

5. The intrinsic viscosity ([η cxis 5. The thermoplastic elastomer composition according to claim 1 , further comprising a propylene-based polymer (B2) having a viscosity index (SPA) of 1.5 dl / g or more and 7.5 dl / g or less.

6. The intrinsic viscosity of the xylene insoluble matter at 20° C. ([η cxis 6. The thermoplastic elastomer composition according to claim 5, wherein the viscosity modulus is 1.5 dl / g or more and 6.0 dl / g or less.

7. The thermoplastic elastomer composition according to any one of claims 1 to 6, which satisfies the following requirement (1'): Requirement (1'): The test piece has an area increase rate S of 4% or more and 15% or less after being immersed in petroleum benzine at 23°C for 24 hours.

8. The thermoplastic elastomer composition according to any one of claims 1 to 7, which satisfies the following requirement (2'): Requirement (2'): The test piece has a volume increase rate V of 55% or more and 115% or less after being immersed in petroleum benzine at 23°C for 24 hours.

9. A molded article comprising the thermoplastic elastomer composition according to any one of claims 1 to 8.

10. An airbag storage cover comprising the thermoplastic elastomer composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Cover for containing air bag

    JP1998265628A

  • Olefin thermoplastic elastomer composition for air bag cover and air bag cover produced therefrom

    JP2000072937A

  • Olefinic thermoplastic elastomer and molded product therefrom

    JP2001279030A

  • Cover for storing air-bag

    JP2002194098A

  • Thermoplastic elastomer composition

    JP2009263470A